The photodegradation processes and mechanisms of polyvinyl chloride and polyethylene terephthalate microplastic in aquatic environments: Important role of clay minerals - Ding, Ling; Yu, Xiaoqin; Guo, Xuetao; Zhang, Yaping; Ouyang, Zhuozhi; Liu, Peng; Zhang, Chi; Wang, Tiecheng; Jia, Hanzhong; Zhu, Lingyan (Water research (Oxford), 2022)
•Photodegradation behaviors of MPs in the presence of clays were firstly explored.•Clay minerals, particularly kaolinite, significantly enhanced the MP photoaging.•The aging of PET was more prominent than PVC.•Clay facilitated the production of •OH, greatly contributing to MP degradation.•Photodegradation mechanism of MPs mediated by clay minerals was disclosed. It is well known that microplastics (MPs) may experience weathering and aging under ultraviolet light (UV) irradiation, but it remains unclear if these processes are impacted by natural components, such as clay minerals. In this study, we systematically investigated the photodegradation behaviors of polyvinyl chloride (PVC) and poly (ethylene terephthalate) (PET), two utmost used plastics, in the presence of clay minerals (kaolinite and montmorillonite). The results demonstrated that the clay minerals, particularly kaolinite, significantly promoted the MPs photodegradation, and the aging of PET was more prominent. The photodegradation was the most distinct at pH 7.0, regardless of the presence or absence of the clay minerals. The results of electron paramagnetic resonance and inhibition experiments of reactive oxygen species indicated that the minerals, particularly kaolinite, remarkably facilitated production of •OH, which was the key species contributing to the photodegradation of MPs. Specifically, UV irradiation facilitated the photo-ionization of MPs, producing hydrated electrons and MP radical cations (MP+). The Lewis base sites prevalent on the clay siloxane surfaces could stabilize the MP radical cations and prevent their recombination with hydrated electrons, which promoted the generation of •OH under aerobic conditions, and facilitated the degradation of MP. Two-dimensional (2D) Fourier transformation infrared (FTIR) correlation spectroscopy (COS) analysis and ultra-high-performance liquid chromatography coupled to a Q Exactive Orbitrap HF mass spectrometer were used to identify the sequential changes of functional groups, and the degradation products of the MPs. This study improves our understanding on the aging of MPs in the complex natural environment. [Display omitted]